Towards a volumetric census of close white dwarf binaries – I. Reference samples. Issue 2 (16th March 2021) - Inight, K; Gänsicke, Boris T; Breedt, E; Marsh, T R; Pala, A F; Raddi, R
ABSTRACT: Close white dwarf binaries play an important role across a range of astrophysics, including thermonuclear supernovae, the Galactic low-frequency gravitational wave signal, and the chemical evolution of the Galaxy. Progress in developing a detailed understanding of the complex, multithreaded evolutionary pathways of these systems is limited by the lack of statistically sound observational constraints on the relative fractions of various sub-populations and their physical properties. The available samples are small, heterogeneous, and subject to a multitude of observational biases. Our overarching goal is to establish a volume-limited sample of all types of white dwarf binaries that is representative of the underlying population as well as sufficiently large to serve as a benchmark for future binary population models. In this first paper, we provide an overview of the project, and assemble reference samples within a distance limit of 300 pc of known white dwarf binaries spanning the most common sub-classes: post-common envelope binaries containing a white dwarf plus a main-sequence star, cataclysmic variables, and double-degenerate binaries. We carefully vet the members of these "Gold" samples, which span most of the evolutionary parameter space of close white dwarf binary evolution. We also explore the differences between magnitude and volume limited close white dwarf binary samples, and discuss how these systems evolve in their observational properties across the Gaia Hertzsprung–Russell diagram.